Length of Hospitalization and Polypharmacy in Diabetes Multimorbidity with Infectious Diseases - Tasrif Ahmad; Hari Saktiningsih; Firdy Permana; Perigrinus Hermin Sebong; Yanri Wijayanti Subronto; Riris Andono Ahmad (Indonesian Journal of Global Health Research, 2022)
Patients with chronic condition have a higher risk of death and disability than others without chronic condition. Meanwhile, low to middle income countries facing challenges in reducing the burden of Non-Communicable Diseases (NCDs) and controlling infectious diseases such as Human Immunodeficiency Virus, Tuberculosis and Malaria. Patients with Diabetes are more often facing infection than people without diabetes. This research aimed to evaluate the length of hospitalization and polypharmacy in patients with multimorbidity of Diabetes with TB, HIV, and Malaria. Design of this research was a retrospective cohort study. All patients diagnosed with Diabetes since 2008 were grouped according to their illnesses to examine the impact of the diseases from the clinical perspective. Data were collected and extracted from the electronic medical records of PT. Freeport Indonesia since 2008. Determination of level of multimorbidities was performed by using principal component analysis, then the clinical impact of those multimorbidities analyzed using ANOVA tests. Multimorbidities have a significant effect on length of stay (p<0.05) and polypharmacy (p<0.05). The highest need for hospitalization and medication was in the Diabetes-Malaria-Tuberculosis group compared to the other multimorbidity groups. Multimorbidities have a significant impact on length of stay and polypharmacy.